3
$\begingroup$

$\newcommand{\expterm}[0]{\frac{-iH(t_2 - t_1)}{\hbar}} \newcommand{\exptermp}[0]{\frac{iH(t_2 - t_1)}{\hbar}}$Nielsen & Chuang (10th edition, page 82) states that $H$ is a fixed Hermitian operator known as the Hamiltonian. In exercise 2.54, we prove that if $A$ and $B$ are commuting Hermitian operators, then the following holds: $$ \exp(A)\exp(B)=\exp(A+B) \tag{1}\label{1} $$

The goal is to prove $$\exp \left[ \expterm \right] \exp \left[ \exptermp \right] = I.\tag{2}\label{2}$$ If $\expterm$ is Hermitian, then we can plug $A=\expterm$ and its Hermitian conjugate $B = \exptermp$ into \eqref{1} to prove \eqref{2}. However, I don't see why $\expterm$ is necessarily Hermitian. Take $H=I$ for example: $H$ is Hermitian but $\expterm$ is not, so we can't use \eqref{1}. Any thoughts?

$\endgroup$
  • 1
    $\begingroup$ Am I missing something here: why isn't $ \frac{-i H(t_2 - t_1)}{h} $ hermitian when $ H $ hermitian? You are just multiplying $H$ by a constant $\endgroup$ – C. Kang Sep 3 at 19:09
  • 1
    $\begingroup$ @C.Kang Let $H \equiv I$ and $K\equiv \frac{-i H(t_2 - t_1)}{h}$. Then $K^\dagger = \left( \frac{-i I(t_2 - t_1)}{h} \right)^\dagger = \frac{i I(t_2 - t_1)}{h}$. So $K^\dagger=-K$ but we need $K^\dagger=K$ for Hermiticity, right? $\endgroup$ – Attila Kun Sep 3 at 20:05
6
$\begingroup$

If $H$ is Hermitian, then $iH$ is not Hermitian, but rather skew-Hermitian: $(iH)^\dagger = -i H^\dagger =-iH$.

Still, the identity in (1) holds generally for commuting matrices, they don't have to be Hermitian:

$$e^{A+B} = \sum_{k=0}^\infty \frac{(A+B)^k}{k!}=\sum_{k=0}^\infty \frac{1}{k!} \sum_{j=0}^k \binom{k}{j} A^j B^{k-j} = \sum_{k=0}^\infty \sum_{j=0}^k \frac{A^j B^{k-j}}{j! (k-j)!} \\ = \sum_{n,m=0}^\infty \frac{A^n B^m}{n! m!} = e^A e^B,$$ where the commutativity was necessary to use Newton's formula in the second step, and in the penultimate step we changed the summation variables with $n=j, m=k-j$.

More generally, $e^A$ is unitary if $A$ is skew-Hermitian, as $$(e^A)^\dagger e^A = e^{A^\dagger} e^A = e^{-A}e^A=I,$$ and similarly for $e^{A}(e^A)^\dagger=I$. Vice-versa, for any unitary $U$ there is always a skew-Hermitian $A$ such that $U=e^A$, see this question on math.SE.

See also this similar question on math.SE.

| improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.